Deconstructing the Cherokee Nation : Town, Region, and Nation among Eighteenth-Century Cherokees - Boulware, Tyler (Book collections on Project MUSE., 2011)
This significant contribution to Cherokee studies examines the tribe's life during the eighteenth century, up to the Removal. By revealing town loyalties and regional alliances, Tyler Boulware uncovers a persistent identification hierarchy among the colonial Cherokee.